2015
DOI: 10.5935/0101-2800.20150073
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic acidosis and its association with nutritional status in hemodialysis

Abstract: The prevalence of metabolic acidosis was high in this population, and a lower BIC correlated with higher levels of urea, PTH, phosphorus, interdialytic weight gain and lower BMI. The evaluation of acid-basic status should be routinely implemented in dialysis patients by considering the negative effects of acidosis on the nutritional status, inflammation and bone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
2
2
0
2
Order By: Relevance
“…[32] Malnutrition, another common condition defined by low serum albumin and a risk factor for poor outcome in renal disease, may be related to acidemia due to an increased protein catabolism, decreased protein synthesis, endocrine abnormalities and inflammation among patients with renal disease. [9,33] Additionally, in our data, we observed significant prevalence of serum bicarbonate lower or higher than 20 mmol/L on high 10-year risk for coronary heart disease (FRS > 20%) during our median follow up time of 60 months. Supportively, the relationship between the three groups of patients according to the serum bicarbonate concentrations and according to the 10-year risk for coronary heart disease by FRS was found statistically significant.…”
Section: Discussionsupporting
confidence: 58%
“…[32] Malnutrition, another common condition defined by low serum albumin and a risk factor for poor outcome in renal disease, may be related to acidemia due to an increased protein catabolism, decreased protein synthesis, endocrine abnormalities and inflammation among patients with renal disease. [9,33] Additionally, in our data, we observed significant prevalence of serum bicarbonate lower or higher than 20 mmol/L on high 10-year risk for coronary heart disease (FRS > 20%) during our median follow up time of 60 months. Supportively, the relationship between the three groups of patients according to the serum bicarbonate concentrations and according to the 10-year risk for coronary heart disease by FRS was found statistically significant.…”
Section: Discussionsupporting
confidence: 58%
“…Malnutrition and anemia have already been reported as specific cardiovascular risk factors for dialysis patients and each of the MIA syndrome components worsens the survival of these patients [ 35 , 36 ]. Malnutrition may be related to metabolic acidosis due to increased protein catabolism, decreased protein synthesis, endocrine abnormalities, and inflammation among dialysis patients [ 37 ]. Metabolic acidosis defined by low serum bicarbonate (<22 mmol/L) is a common condition in end stage renal disease patients resulting in inflammatory stimulation, lipids oxidation, and oxidative stress [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased CO 2 CP has been demonstrated to be an indicator of metabolic acidosis in patients without respiratory disease. 2 Previous studies have shown that metabolic acidosis is associated with insulin resistance, 3 hypertension, 4 inflammation, 5 activation of the renin-angiotensin-aldosterone system 6 and endothelial dysfunction, 7 all of which can contribute to adverse clinical outcomes after stroke. 3 8 Furthermore, acidosis is common and has been proven to be associated with poor outcomes in ischaemic stroke.…”
Section: Introductionmentioning
confidence: 99%